2021
DOI: 10.3390/en14175282
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities in Measuring Multiscale Pore Structure of the Continental Shale of the Yanchang Formation, Ordos Basin, China

Abstract: Pores of shale exhibit multiscale characteristics, and pore characterization is challenging due to the complexity of pore systems. Currently, research is focused on nano-submicron pores, but the structure of micrometer-scaled pores is not well understood. In this research, an investigation of the three-dimensional pore network of the Chang 7 shale in the Ordos Basin of China was conducted, in order to provide an insight into the full characteristics of pore systems. Nano-CT and micro-CT scanning technology was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These advances have significantly enhanced our understanding of the influence of resolution on the visualization and analysis of pore structures, contributing to the optimization of geothermal reservoir performance. This approach is analogous to that of [20], who employed both nano-CT and µ-CT to investigate multi-scale pore structures in shale. They applied segmentation techniques to high-resolution µ-CT images in order to enhance the quantification and spatial distribution of pore networks.…”
Section: Introductionmentioning
confidence: 99%
“…These advances have significantly enhanced our understanding of the influence of resolution on the visualization and analysis of pore structures, contributing to the optimization of geothermal reservoir performance. This approach is analogous to that of [20], who employed both nano-CT and µ-CT to investigate multi-scale pore structures in shale. They applied segmentation techniques to high-resolution µ-CT images in order to enhance the quantification and spatial distribution of pore networks.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al 31 investigated the pore space connectivity in Longmaxi shale using the spontaneous fluid imbibition method and suggested that oil‐wet regions were better connected than water‐wet regions; however, the degree of connectivity was not studied further. Tang et al 32 and Li et al 33 used nano‐CT to evaluate pore connectivity in shale; however, the maximum resolution used was only 60 nm, which could not meet the needs of nano‐pore system analysis in OM. Compared with nano‐CT, 3D FIB‐SEM technology can provide a three‐dimensional (3D) reconstruction model with a high resolution of a few nanometers based on numerous two‐dimensional (2D) images, providing opportunities for quantitative evaluation of the 3D structure of OM pores.…”
Section: Introductionmentioning
confidence: 99%